Faktor-Faktor Yang Menyebabkan Burnout Pada Pekerja Lepas Pantai (Offshore) - Sutrisno, Sutrisno; Soesanto, Edy; Indanah, Indanah; Yulisetyaningrum, Yulisetyaningrum; Faiqh Albyn, Devanda (Medical : Jurnal Kesehatan dan Kedokteran, 2024)
Background: The major impact of burnout on overseas workers, such as inadequate physical and psychological working conditions, has been proven to be associated with adverse health outcomes among workers, including the emergence of various diseases, increased stress levels, reduced concentration which can lead to the occurrence of work accidents which end in decreased productivity. This impact is a small part of the concept of Occupational Diseases (PAK) which is one of the pillars of Occupational Health and Safety. Objective: to find out the factors that cause burnout in offshore workers. Method: This research is an observational analysis research with a cross-sectional approach, where the researchers only observed offshore workers on the Belait CSS-1 ship. Samples were selected using a non-probability purposive sampling technique to obtain 80 samples. Results: There is a relationship between age (p = 0.021), education (p = 0.000), marital status (p = 0.021), length of service (p = 0.038), type of work (p = 0.000), work stress (p = 0.000 ), and workload (p = 0.003) with burnout in offshore workers. Conclusion: There are various factors that can influence burnout in offshore workers such as age, education, type of work, work stress and length of service..